Combined calcitriol and menadione reduces experimental murine triple negative breast tumor - Bohl, Luciana Paola (2017)
Background Calcitriol (D) or 1,25(OH)2D3 inhibits the growth of several tumor cells including breast cancer cells, by activating cell death pathways. Menadione (MEN), a glutathione-depleting compound, may be used to potentiate the antiproliferative actions of D on cancer cells. We have previously shown in vitro that MEN improved D-induced growth arrest on breast cancer cell lines, inducing oxidative stress and DNA damage via ROS generation. Treatment with MEN + D resulted more effective than D or MEN alone. Objective: To study the in vivo effect of calcitriol, MEN or their combination on the development of murine transplantable triple negative breast tumor M-406 in its syngeneic host. Methods Tumor M-406 was inoculated s.c., and when tumors reached the desired size, animals were randomly assigned to one of four groups receiving daily i.p. injections of either sterile saline solution (controls, C), MEN, D, or both (MEN + D). Body weight and tumor volume were recorded three times a week. Serum calcium was determined before and at the end of the treatment, at which time tumor samples were obtained for histological examination. Results None of the drugs, alone or in combination, affected mice body weight in the period studied. The combined treatment reduced tumor growth rate (C vs. MEN + D, P < 0.05) and the corresponding histological sections exhibited small remaining areas of viable tumor only in the periphery. A concomitant DNA fragmentation was observed in all treated groups and MEN potentiated the calcitriol effect on tumor growth. Conclusions As previously observed in vitro, treatment with MEN and D delayed tumor growth in vivo more efficiently than the individual drugs, with evident signals of apoptosis induction. Our results propose an alternative protocol to treat triple negative breast cancer, using GSH depleting drugs together with calcitriol, which would allow lower doses of the steroid to maintain the antitumor effect while diminishing its adverse pharmacological effects.